The effect of mechanical lymph drainage accompanied with heat on lymphedema. - Mariana, Valente Flavia; de Fatima, Guerreiro Godoy Maria; Maria, Pereira de Godoy Jose (Journal of Research in Medical Sciences, 2011)
BACKGROUND: Thermotherapy has been indicated by some researchers as a treatment for lymphedema. A study comparing temperatures demonstrated that a temperature of 40ºC significantly increased the transportation of lymph compared to other temperatures assessed. The aim of this study was to evaluate the possible benefits of mechanical lymph drainage accompanied with heat in the treatment of lymphedema of the lower limbs. METHODS: In a cross-over randomized study, the effect of heat on lymph drainage was evaluated in the treatment of leg lymphedema. The study, performed in the Godoy Clinic in São Jose do Rio Preto, Brazil, involved seven patients (two males and five females) with leg lymphedema. The patients' ages ranged from 18 to 79 years old with a mean of 48.5 years. The subjects underwent a total of 38 assessments including 19 evaluations of mechanical lymph drainage alone and 19 combined with thermotherapy. Heat was applied using an electric blanket which was wrapped around the legs of the patients. The volume of legs was evaluated by water plethysmography before and after treatment sessions. The paired t-test was used for statistical analysis with an alpha error of p = 0.05 being considered as acceptable. RESULTS: No statistically significant differences were evidenced between mechanical lymph drainage alone and lymph drainage combined with thermotherapy. CONCLUSIONS: There was no obvious synergic effect in the immediate post-treatment period when heat was combined with mechanical lymph drainage in the treatment of lymphedema.